Works council introductions in Germany: Do they reflect workers' voice?. (May 2019) - Oberfichtner, Michael
While most previous studies focus on the monopoly aspect of works council introductions, this article explores the collective voice face of introductions and investigates workers' decision as an exit–voice consideration. Using a large linked employer–employee dataset from Germany, the present study finds that council introductions are more likely if workers have high plant-specific human capital or earn high wages. These results are consistent with exit–voice considerations as well as with attempts to protect an existing distribution of rents. Redoing the analysis for plants in which the protection of rents against management decisions is less relevant yields similar results supporting a voice interpretation.